2008
DOI: 10.1080/08961530802129490
|View full text |Cite
|
Sign up to set email alerts
|

A Branding Strategy for Emerging Market Firms Entering Developed Markets

Abstract: Firms from emerging markets face several challenges when entering and trying to compete in developed markets. One of these obstacles to success is the negative counlry of origin effects that these firms face. By viewing the country of origin phenomenon through the lens of signaling theory, we propose that firms can reduce the noise caused by the made in... label by adopting a branding strategy that cotisumers connote with a positive country image. In an experiment focusing on brand names from Hungary and Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
2
28
1
4
Order By: Relevance
“…For instance, the German supermarket chain Aldi sells German-made pastas and pizzas under the brand name Mama Mancini and the slogan "La cucina tradizionale" in order to suggest Italy as the product's COO. Similarly, companies originating from countries with low perceived product quality and/or country image (e.g., developing countries) can benefit from a foreign slogan or a foreign brand name (e.g., Magnusson, Haas, and Zhao 2008;Melnyk et al 2012). An additional advantage of using FLs is that they may lead to better ad liking than a COO mention, as Study 3 has indicated.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…For instance, the German supermarket chain Aldi sells German-made pastas and pizzas under the brand name Mama Mancini and the slogan "La cucina tradizionale" in order to suggest Italy as the product's COO. Similarly, companies originating from countries with low perceived product quality and/or country image (e.g., developing countries) can benefit from a foreign slogan or a foreign brand name (e.g., Magnusson, Haas, and Zhao 2008;Melnyk et al 2012). An additional advantage of using FLs is that they may lead to better ad liking than a COO mention, as Study 3 has indicated.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…mostrando-se ser uma empresa local (Tallman & Yip, 2009); comprando uma marca local (Demirbag, Sahadev & Mellahi, 2010) ou construindo sua identidade a partir de um terceiro país (Tallman & Yip, 2009;Magnusson et al, 2008) escolhendo um nome ocidental para a marca (Herstein, et al, 2014).…”
Section: Os Processos De Incorporação Da Coi E Elaboração De Hipótesesunclassified
“…No entanto, a COI do país emergente pode mostrar-se um recurso valioso em operações internacionais (Cuervo-Cazurra & Un, 2015;Kumar & Steenkamp, 2013;Chattopadhyay et al, 2012;Magnusson et al, 2008), dependendo da maneira como a empresa emprega esse recurso na marca (Magnusson et al, 2008) e no modo como o país de destino (consumidores e governo) percebe a imagem do país de origem da empresa (Cuervo-Cazurra & Un, 2015). Para Kumar & Steenkamp (2013) as empresas de mercados emergentes podem tornar suas marcas globais.…”
Section: Os Processos De Incorporação Da Coi E Elaboração De Hipótesesunclassified
See 1 more Smart Citation
“…Contudo, já se sabe que este conceito usualmente desafia empresas de países emergentes em vez de beneficia-las (Josiassen & Harzing, 2008;Pappu, Quester, & Cooksey, 2007). Isto por que consumidores de mercados desenvolvidos tendem a avaliar produtos desenvolvidos em mercados emergentes de modo negativo, ao associa-los com baixa qualidade e baixo custo (Magnusson, Haas, & Zhao, 2008;Manrai, Lascu, & Manrai, 1998). Alguns autores acreditam que organizações provenientes de mercados emergentes podem minimizar os efeitos negativos da imagem do país de origem, ajustando o posicionamento da marca e associando-a com imagens positivas que agradariam ao consumidor com o uso de ações de marketing (Sutter, Maclennan, Polo, & Strehlau, 2016).…”
unclassified